Perendaman Menggunakan Ekstrak Buah Mengkudu (Morinda Citrifolia L.) dan Pengaruhnya terhadap Sifat Fisik Daging Kuda Lokal yang Telah Dibekukan - Lestari, Ayu; Putra, Rezki Anugrah; Mutmainna, Andi; Irmawaty, Irmawaty; Jamili, Muhammad Arsan (Anoa: Journal of Animal Husbandry, 2024)
Meat that has been frozen will experience a decline in physical quality, so to keep its physical properties in good condition, processing technology is needed to maintain the physical properties of horse meat. The aim of the research was to determine the effect of soaking using noni fruit extract (Morinda citrifolia l.) on the physical properties of frozen local horse meat. The research method used was a completely randomized design with 4 treatments and 3 replications. Factor A concentration of noni fruit extract (Morinda citrifolia L.) was 0% (A0), 10% (A1), 15% (A2) 20% (A3) with a soaking time of 30 minutes. Data analysis used Analysis of Variance (ANOVA) and the Honest Significant Difference (BNJ) test. Based on the results of research regarding the effect of soaking local horse meat with noni fruit extract at different concentrations using meat that had been frozen, the results were obtained that soaking with noni fruit extract had no effect on the water holding capacity, breaking strength of the meat and pH, but had a very significant effect on shrinkage cook frozen local horse meat.